Synthesis and characterization of fluorescent PVA/pvac-rodhamine microspheres - Ambrosio Tellez, Luisa Fernanda (2019)
Fluorescent polymeric microspheres are used in a wide range of biomedical and technological applications, including blood flow determination, screening, flow visualization, flow tracing, medical imaging, fluorescence microscopy and flow cytometry among others. Rhodamine 6G (R6G) is a lipophilic cationic dye, which is among the most stable organic fluorophores, and with a high quantum yield in fluorescence (absorption and emission) in the visible range (500-600 nm). It is mainly applied in laser technology, and also in fluorescent bioimage. In this work we present an efficient synthesis route to obtain Polyvinyl Alcohol/Polyvinyl Acetate (PVA/PVAc) spherical microparticles containing Rhodamine 6G in a concentration sufficient to exploit their fluorescent properties. The synthesis method comprises the suspension polymerization of Vinyl acetate (VAc) monomer in the presence of Rhodamine, followed by saponification. Microspheres loaded with 1.9% w / w of Rhodamine 6G were obtained. They presented good sphericity and a size distribution in the range of 20 to 1550 microns. The fluorescence intensity of the microspheres was measured by UV-Vis and fluorescence spectroscopy, and detected using an image-based experimental setup, respectively. The results obtained with these methodologies showed that our microspheres exhibit fluorescence and that they are quite detectable in water flows. However, the response of UV-Visible fluorescence and absorbance was affected by the presence of the PVA / PVAc polymer matrix.